A New Model of Patient Monitoring System for Lymphatic Treatment of Leg Pain based on Double-Loop Feedback Theory - Abdul Wahid, Fauziah; Muhammed Suzuki, Siti Aishah; Md Norwawi, Norita (Malaysian Journal of Science Health & Technology, 2021)
Leg pain occurs in many people nowadays due to today’s lifestyle. This leads to the development of various treatments for leg pain. However, there are some issues regarding the existing leg pain treatments. The first issue is the treatment method where most treatments for leg pain use compression but they are costly, time-consuming and cumbersome, which require patients to visit hospitals regularly that affect patient’s compliance to continue with treatments. The second issue is the treatment time frame for leg pain is within a short time frame, whereby it is difficult to see the major effect of a certain treatment. The third issue is the lack of a system to monitor the patient’s rehabilitation progress to increase patients’ confidence to continue treatment consistently to cure their leg pain. Therefore, this research is conducted to cover all issues of existing research under the main area of health informatics. This research will be conducted in Nilai, Negeri Sembilan where 30 respondents with leg pain problems will be chosen as samples of this research and treatment will be conducted for 6 months. The treatment method is by using fingertips massage with oral and topical medication, where oral medication is disregard herb-based pills and topical medication is cinnamon cream. This system is needed to help patients to resolve their leg pain through the lymphatic treatment model. This lymphatic treatment model for leg pain resolution will be a useful guide for all patients with leg pain and also the caretaker of that patient. It requires a low cost and especially beneficial to lower to the middle-class community. This research is significant for the national agenda as it falls under the national research priority area of Health and Medicine. The expected outcome of this research is a new concept of the systematic patient monitoring system for lymphatic treatment of leg pain based on double-loop feedback theory.